Alpha Oscillations in Parietal and Parietooccipital Explaining How Boredom Matters Prospective Memory - Chen, Pin-Hsuan; Rau, Pei-Luen Patrick (Frontiers in Neuroscience, 2022)
Intelligent interaction alters previous human-machine task allocation patterns. Human workers will suffer from boredom and inattention, posing a significant challenge for the human-machine interaction loop. This study aims to investigate the relationship between boredom and prospective memory, which is a memory form including the detecting, identifying, executing functions. Thus, the attention and memory mechanisms are critical to complete prospective memory tasks when bored. This study recruited twenty-eight participants and used electroencephalography to measure the alpha power in brain regions. The results indicated that parietal oscillations had a mediate effect on prospective memory, which could be associated with the frequent unstable attention. Additionally, this study found that parietooccipital oscillations linked boredom and prospective memory, and the default mode network and visual processing during boredom could better explain this finding. The findings of this study suggested that attention management and influences of processing visual information were starting points to cope with boredom because they could help prepare for prospective memory and making optimal decisions accordingly.